1998
DOI: 10.1002/jor.1100160605
|View full text |Cite
|
Sign up to set email alerts
|

Single local injection of recombinant fibroblast growth factor‐2 stimulates healing of segmental bone defects in rabbits

Abstract: The effects of a single local injection of recombinant human fibroblast growth factor-2 on the healing of segmental bone defects were evaluated in rabbits. One month after the external fixator originally designed for this experiment was installed in the tibia of the rabbit, a 3-mm bone defect was created by an osteotomy in the middle of the tibia and 0, 50, 100, 200, or 400 microg of fibroblast growth factor-2 in 100 microl of saline solution was injected into the defect. Injection of the growth factor increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
102
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(106 citation statements)
references
References 39 publications
2
102
0
2
Order By: Relevance
“…Given at high concentrations, bFGFs and other growth factors have a toxic effect. Their biological efficacy after a one-dose local application at the concentrations we selected, namely 1-100 ng bFGF, and also at much higher doses, has been verified in numerous publications (Joseph-Silverstein and Rifkin 1987, Sprugel et al 1987, Broadley et al 1989, Burges 1989, Rifkin and Moscatelli 1989, Klingbeil et al 1991, Albertson et al 1993, Kawaguchi et al 1994, Nagai et al 1995, Okumura et al 1996, Leunig et al 1997, Kato et al 1998, McGee et al 1998. With the exception of one study , local application of the appropriate growth factor led to an acceleration of wound and fracture healing in all of the above studies.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Given at high concentrations, bFGFs and other growth factors have a toxic effect. Their biological efficacy after a one-dose local application at the concentrations we selected, namely 1-100 ng bFGF, and also at much higher doses, has been verified in numerous publications (Joseph-Silverstein and Rifkin 1987, Sprugel et al 1987, Broadley et al 1989, Burges 1989, Rifkin and Moscatelli 1989, Klingbeil et al 1991, Albertson et al 1993, Kawaguchi et al 1994, Nagai et al 1995, Okumura et al 1996, Leunig et al 1997, Kato et al 1998, McGee et al 1998. With the exception of one study , local application of the appropriate growth factor led to an acceleration of wound and fracture healing in all of the above studies.…”
Section: Discussionmentioning
confidence: 58%
“…Clinical and animal experiments have shown that local application of growth factors may accelerate this restoration of vascularization/perfusion and lead to improvement of wound and fracture healing (Mustoe et al 1987, Sprugel et al 1987, Rifkin andMoscatelli 1989, Klingbeil et al 1991, Yasko et al 1992, Albertson et al 1993, Lind et al 1993, Kawaguchi et al 1994, Nash et al 1994, Nielsen et al 1994, Steenfos et al 1994, Heckman et al 1995, Nagai et al 1995, Richard et al 1995, Okumura et al 1996, Wang and Aspenberg 1996, Beer et al 1997, Davidson et al 1997, Leunig et al 1997, Bostrom and Camacho 1998, Kato et al 1998, McGee et al 1998, Wieman et al 1998, Corral et al 1999, Radomsky et al 1999, Bouxein et al 2001, Govender et al 2002, Luppen et al 2002, Einhorn et al 2003, Hom and Manivel 2003.…”
mentioning
confidence: 99%
“…54 Several biological factors, such as TGFb, BMP, FGF, PDGF, IGF, and LMP-1, have been investigated for their potential use in bone regeneration and skeletal repair. [55][56][57][58][59][60][61][62][63][64][65][66][67][68][69] BMPs have been shown to be the most promising, and clinical trials with recombinant BMP-2 and -7 are ongoing. 54,[70][71][72][73] These BMPs have shown varying degrees of success in the clinical setting and further study on their mechanisms of action and optimal formulations is required to optimize effectiveness of this strategy for promoting osteogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…After approval of the protocol by the Institutional Review Boards (IRB) at all participating institutions and after the patients had provided written informed consent, patients were assigned in order of enrollment to one of three investigational groups that received a total dosage of 200, 400, or 800 mg of rhFGF-2 in a biodegradable gelatin hydrogel carrier (the total reconstituted volume was 1 mL). The rhFGF-2 dosages were determined based on previous preclinical results of osteotomy experiments on rats, rabbits, dogs, and monkeys [7][8][9]12 through normalizing by the cross section area of the bones. Safety of a dosage was assessed and confirmed before proceeding to a higher trial dosage.…”
Section: Methodsmentioning
confidence: 99%
“…We and others have reported the anabolic effect of local and systemic administrations of FGF-2 on bone formation using several animal models including nonhuman primates. [6][7][8][9][10][11][12][13][14][15] A single local application of FGF-2 facilitated the healing of bone fracture and segmental bone defect in normal and diabetic rats, rabbits, dogs, and monkeys; [6][7][8][9][10][11][12] stimulated bone formation in callotasis bone lengthening in rabbits; 13 and increased bone mass intraosseously in normal and ovariectomized rats and rabbits. 14 In addition, a daily systemic administration of FGF-2 facilitated endosteal bone formation.…”
Section: Introductionmentioning
confidence: 99%